2022
DOI: 10.3389/fimmu.2022.1057181
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated crosstalk between cancer stem cells and their inflammatory niche from the colorectal precancerous adenoma stage to the cancerous stage: Mechanisms and clinical implications

Abstract: The majority of colorectal cancers (CRCs) are thought to arise from precancerous adenomas. Upon exposure to diverse microenvironmental factors, precancerous stem cells (pCSCs) undergo complex genetic/molecular changes and gradually progress to form cancer stem cells (CSCs). Accumulative evidence suggests that the pCSC/CSC niche is an inflammatory dominated milieu that contains different cytokines that function as the key communicators between pCSCs/CSCs and their niche and have a decisive role in promoting CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 189 publications
0
1
0
Order By: Relevance
“…Eliminating cancer stem cells, which are at the apex of a hierarchy prevalent in numerous cancer types, is regarded as a crucial aspect of effective antitumor treatment [126]. Precancerous stem cells (pCSCs) undergo complicated genetic and molecular alterations when exposed to diverse microenvironmental variables, leading to the slow transformation of precancerous stem cells into colon cancer stem cells, which is assumed to be the origin of most colorectal malignancies [127].…”
Section: The Role Of Emt In Tumor Stroma and Crc Stem Cellsmentioning
confidence: 99%
“…Eliminating cancer stem cells, which are at the apex of a hierarchy prevalent in numerous cancer types, is regarded as a crucial aspect of effective antitumor treatment [126]. Precancerous stem cells (pCSCs) undergo complicated genetic and molecular alterations when exposed to diverse microenvironmental variables, leading to the slow transformation of precancerous stem cells into colon cancer stem cells, which is assumed to be the origin of most colorectal malignancies [127].…”
Section: The Role Of Emt In Tumor Stroma and Crc Stem Cellsmentioning
confidence: 99%
“…Extracellular vesicles, including exosomes, as well as soluble factors such as interleukins, cytokines, and other metabolites are found in the tumor microenvironment (TME) [21][22][23]. These factors contribute to the establishment of a specialized tumor niche by attracting stromal cells, modulating angiogenesis, promoting metastasis, conferring resistance to anti-tumor treatments, and maintaining CSCs themselves through the secretion of specific molecules like IL-6, VEGF, and TGF-ß [24][25][26].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…STAT6, a signal transducer and activator of transcription 6, has shown promise as a powerful target for anti-cancer medications [ 15 , 16 ]. Clinical evidence reveals a positive correlation between high levels of STAT6 expression and poor clinical outcomes in colorectal cancer patients [ 17 ]. A previous study demonstrated that STAT6-deficient mice displayed fewer and smaller colorectal tumors compared to wild-type mice [ 18 ].…”
Section: Introductionmentioning
confidence: 99%